2019
DOI: 10.3390/md17120673
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Suppresses Cigarette Smoke-Induced Emphysema through Nrf2 Activation in Mice

Abstract: Oxidative stress plays an important role in the pathogenesis of chronic obstructive pulmonary disease (COPD). The activation of nuclear factor erythroid 2-related factor 2 (Nrf2) is a key cellular defense mechanism against oxidative stress. Recent studies have shown that astaxanthin protects against oxidative stress via Nrf2. In this study, we investigated the emphysema suppression effect of astaxanthin via Nrf2 in mice. Mice were divided into four groups: control, smoking, astaxanthin, and astaxanthin + smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 51 publications
4
28
1
2
Order By: Relevance
“…The cigarette smoke-exposed mice showed less weight gain, increased inflammatory cell infiltration in BALF, and development of emphysema characterized by alveolar enlargement and greater destruction of alveoli, similar to mice in a previous report. 23 , 33 , 34 Our results showed a discrepancy regarding the effect of NYT on smoking-induced change in pulmonary morphology: NYT induced partial recovery of alveolar damage as indicated by the DI; however, NYT did not reduce air space enlargement as indicated by the MLI. Some reports showed that the DI is a more sensitive parameter of pulmonary destruction than the MLI, 30 , 35 whereas others revealed a correlation between the MLI and loss of elastic recoil.…”
Section: Discussioncontrasting
confidence: 61%
“…The cigarette smoke-exposed mice showed less weight gain, increased inflammatory cell infiltration in BALF, and development of emphysema characterized by alveolar enlargement and greater destruction of alveoli, similar to mice in a previous report. 23 , 33 , 34 Our results showed a discrepancy regarding the effect of NYT on smoking-induced change in pulmonary morphology: NYT induced partial recovery of alveolar damage as indicated by the DI; however, NYT did not reduce air space enlargement as indicated by the MLI. Some reports showed that the DI is a more sensitive parameter of pulmonary destruction than the MLI, 30 , 35 whereas others revealed a correlation between the MLI and loss of elastic recoil.…”
Section: Discussioncontrasting
confidence: 61%
“…In addition, the number of inflammatory cells in the bronchoalveolar lavage fluid was significantly reduced and emphysema was significantly suppressed in the ASX groups. In conclusion, ASX protects against oxidative stress by activating the Nrf2 pathway and improves cigarette smoke-induced emphysema [ 61 ].…”
Section: Major Biochemical Pathways Involved In Astaxanthin Pro-lomentioning
confidence: 99%
“…Astaxanthin is a carotenoid, widely distributed in marine life such as shrimp and crab. It has been reported to improve smoking-induced emphysema and inhibit oxidative stress by activating Nrf2 and HO-1, providing a new treatment option for COPD [ 79 ]. Moreover, sulforaphane can protect lung epithelial cells by decreasing ROS levels and upregulating the expression of Nrf2 [ 57 , 58 ].…”
Section: Bioactive Compounds In Food In Chronic Diseasesmentioning
confidence: 99%